Lumican modulates adipocyte function in obesity-associated type 2 diabetes. (31st December 2022) - Strieder-Barboza,; Flesher, Carmen G.; Geletka, Lynn M.; Eichler, Tad; Akinleye, Olukemi; Ky, Alexander; Ehlers, Anne P.; Lumeng, Carey N.; O'Rourke, Robert W.
ABSTRACT: Obesity-associated type 2 diabetes (DM) leads to adipose tissue dysfunction. Lumican is a proteoglycan implicated in obesity, insulin resistance (IR), and adipocyte dysfunction. Using human visceral adipose tissue (VAT) from subjects with and without DM, we studied lumican effects on adipocyte function. Lumican was increased in VAT and adipocytes in DM. Lumican knockdown in adipocytes decreased lipolysis and improved adipogenesis and insulin sensitivity in VAT adipocytes in DM, while treatment with human recombinant lumican increased lipolysis and impaired insulin-sensitivity in an ERK-dependent manner. We demonstrate that lumican impairs adipocyte metabolism, partially via ERK signalling, and is a potential target for developing adipose tissue-targeted therapeutics in DM.